Identifying potential groundwater recharge zones using the Analytic Hierarchy Process (AHP) method, in the Upper-Middle Drâa Basin, Morocco - Hayat, Ghachoui; Adbelhalim, Tabit; Ahmed, Algouti; Maryam, Errami; Said, Moujane (Geologos, 2025)
Groundwater is a vital resource sustaining domestic supply, agriculture, and industry, particularly in arid regions where water scarcity severely limits development. Identifying potential groundwater recharge zones is therefore essential for the sustainable management of this resource. This study assesses the spatial distribution of groundwater recharge potential in the Upper-Middle Drâa Basin, southeastern Morocco, which extends over approximately 23,000 km2. The Analytic Hierarchy Process (AHP) was applied within a Geographic Information System (GIS) framework using multi-source geospatial data, including Sentinel-2 imagery and the Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) Digital Elevation Model. The results indicate that high-recharge zones are mainly concentrated in low-slope alluvial plains and along major drainage networks, whereas the surrounding highlands exhibit moderate to low recharge potential. Validation using field data from borehole discharge measurements confirms this spatial pattern, with flow rates ranging from about 1.5 L/s in peripheral sectors to over 6 L/s in central parts of the basin. The strong agreement between model outputs and field observations demonstrates the reliability of the adopted approach and enhances understanding of the basin’s hydrogeological functioning. Overall, this work provides an effective decision-support tool for regional water resource planning and sustainable groundwater management in arid and semi-arid environments.